Why Muslim Countries under developed? - Aisyah, Siti (AL- IKTISAB Journal of Islamic Economic Law, 2017)
Islam is very comprehensive religion as the way of life that guides mankind in allaspects of life. The two responsible of human such as worshiper of Allah and agent ofeconomic on earth are related to development. Nowadays, the development of Islamiceconomic and finance in many Muslim countries is significant to contribute the economicgrowths in the country in spite of many of Muslim countries are still in the povertyproblem. By then, the paper attempts to analyze the major problem of Muslim countriestoward development, to explore determinant factors of development in Islamic goldenage and to give best solution to economic development of Muslim countries. It isqualitative research by using content analysis to answer all reseach questions. Thefindings are that The problem of development in Muslim countries is very complex suchas poverty, lack of human skill, income inequality, low level productivity, accumulationof foreign debt and illiteracy. There are several countries that have excessive oil can becategorized as high human development. The economic development of Islamic Goldenage applies religious and physical factors to promote society welfare. Lastly, there arefive successfull determinant factors in economic development such as religion, knowledge,wealth, inovation and institution.